Meat quality of Santa Inês sheep fed forage palm (Opuntia ficus-indica, Mill) and water restriction - PORTO FILHO, José Matias; COSTA, Roberto; MEDEIROS, Ariosvaldo Nunes; ARAÚJO FILHO, José Teodorico; CRUZ, George Rodrigo Beltrão da; MASCARENHAS, Nágela Maria Henrique; SOUSA, Francisco de Assys Romero Mota; GURJÃO, Thyago Araújo; OLIVEIRA , Larissa Silva Nelo; RIBEIRO, Neila Lidiany (Food Science and Technology, 2024)
The aim of this study was to evaluate the physicochemical composition, fatty acids, and sensory properties of meat from Santa Inês sheep fed forage palm in the diet and with water restriction. They used 42 non-castrated male Santa Inês lambs, with about 180 days of age and an average weight of 21.6 ± 2.2 kg, distributed in a completely randomized design with seven treatments and six repetitions, and the data were submitted to regression analysis, factorial (level × water), and contrast between the control treatment and others. The treatments consisted of the inclusion of spineless cactus (0, 30, 50, and 70%). In treatments containing cactus pear (36 animals), half of the animals were placed under voluntary water consumption restriction. According to the physicochemical characteristics analyzed, lipids suffered an increasing linear effect (p<0.05) as they included spineless cactus in the diet of sheep. The control diet had the lowest percentage of lipids (2.44%). The inclusion of 50% cactus pear promoted a higher content of lipids (3.41), and restricting water intake resulted in higher lipid content (3.09). The inclusion of cactus pear and water restriction did not affect the profile of fatty acids in meat. In the studied sensory attributes (hardness, juiciness, flavor, color, aroma, and overall acceptability), only meat color suffered an increasing linear effect (p < 0.05). With the inclusion of spineless cactus in the diet, the meat from the lambs received good grades from the panelists, showing good acceptability. This demonstrates that the cactus pear provides sufficient water and nutrients for animals, resulting in the deposition of intramuscular fat, thus becoming a good-quality meat.